Study of SNRPN genetic and epigenetic mutations in Prader-Willi and Angelman patients - Chernushyn, S.Yu.; Hryshchenko, N.V. (Вiopolymers and Cell, 2018)
Prader-Willi (PWS) and Angelman (AS) syndromes are two clinically distinct genetic diseases associated with multiple physical and cognitive abnormalities. The genetic cause of PWS and AS is the alteration in the 15q11.2-q13 chromosomal region; expression of genes in this region is subject to genome imprinting. Aim. To analyse of the frequency of 15q11.2-q13 rearrangements and epigenetic alterations in the group of Ukrainian patients with PWS and AS. Methods. The methylation status of the SNRPN gene was analyzed by methylation-specific PCR (MS-PCR). Results. The absence of unmethylated CpGs in the SNRPN gene promoter was detected in 25 patients (42 %) with the PWS phenotype. In the AS group, the frequency of SNRPN mutations (absence of the hypermethylated CpGs) was observed in 28% of the cases. In the PWS, group we observed a significant prevalence of males (70 %), but the frequency of the confirmed diagnosis was higher in females (56% vs. 36%). A lower than expected detection rate in the PWS and AS groups could be due to both clinical and method limitations. Conclusions. Analysis of the SRNPN gene region by MS-PCR could be used for the PWS and AS molecular diagnostics. This test can rule out the clinical diagnosis of PWS in ~ 60 % of Ukrainian patients with suspected PWS and confirm AS in ~30% of patients.